Factors that affect stock market indices: study on finance and properties index in bursa Malaysia / Nur Azlina Abdullah - Abdullah, Nur Azlina (2008)
An index can be defined as an indicator, which enables one to reach a conclusion in a fast and correct way by considering various different variables in a combined way. Indices for all stock markets are composed in order to calculate price and return performances of all shares. By this way, investors can have an overall idea about the market. This paper discussed the factors that affect stock market indices in Bursa Malaysia. This research concentrated on finance and properties index as dependent variables while four macroeconomic variables namely interest rate (BLR), inflation rate (Consumer Price Index), exchange rate (RM against US Dollar), and money supply (M2) as independent variables. As for methodology, the analysis of this study covers a period of 10 years from 1998 to 2007 based on monthly basis. Method that this research used is Multiple Regression Analysis Method. By using this method, this study could see whether there is a significant correlation between all of the independent variables and dependent variables. From this study, it was found that all of the independent variables have significance correlation with dependent variables. From multiple regression model 1 and 2, the both results found that interest rate (BLR), inflation rate (CPI) and exchange rate of RM/US Dollar have a negative relationship with dependent variables that are finance and properties index in Bursa Malaysia. However, from both results, money supply (M2) has a positive relationship with finance and properties index in Bursa Malaysia.